SOR as Adjuvant Therapy after Resection for Pancreatic Cancer Does Not Improve DFS - Kuznar, Wayne (MD Conference Express, 2014)
Even after successful surgery intended as curative, up to 90% of patients with pancreatic cancer suffer a relapse. Adding sorafenib to gemcitabine as adjuvant therapy for patients after R1 resection for pancreatic cancer does not improve disease-free survival or overall survival compared with GEM alone. This article presents results from the phase 2b CONKO-006 study.